Polymer composite and molded article containing same

JP7636098B2Active Publication Date: 2025-02-26LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023555641
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-24
Filing Date
2022-07-13
Publication Date
2025-02-26
Estimated Expiration
2042-07-13

AI Technical Summary

Benefits of technology

【0111】 本発明による高分子複合体は補強材としてセルロース繊維を含んで環境に優しく、かつ優れた機械的物性と高い明度値を示すことができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636098000005
    Figure 0007636098000005
  • Figure 0007636098000006
    Figure 0007636098000006
  • Figure 0007636098000007
    Figure 0007636098000007
Patent Text Reader

Abstract

The present invention relates to a polymer composite and a molded article containing the same. According to the present invention, there is provided a polymer composite that contains cellulose fiber as a reinforcing material, is environmentally friendly, and exhibits excellent mechanical properties and high brightness.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Cross-reference to related applications This application claims the benefit of priority to Korean Patent Application No. 10-2021-0107618 filed on August 13, 2021, and Korean Patent Application No. 10-2022-0077703 filed on June 24, 2022, and all contents disclosed in the documents of the relevant Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to polymer composites containing a reinforcing material comprising cellulose fibers and molded articles containing the same. [Background technology]

[0003] Pulp is a lignocellulosic fibrous material obtained by chemically or mechanically separating cellulose fibers from wood, fiber crops, waste paper, rags, etc. Cellulosic fibers are mainly used in the papermaking industry and are utilized as a raw material for nanocellulose.

[0004] Nanocellulose is being used in research to improve the physical properties of polymers by combining them with polymers. Unlike those that use glass fiber as a reinforcing material, polymer composites that use environmentally friendly nanocellulose have the advantage of being easily recycled.

[0005] However, the process of producing nanocellulose from cellulose fibers is complicated and costly. In addition, there is a problem that cellulose fibers deteriorate due to the high process temperature during the composite process with polymers. In addition, cellulose fibers and nanocellulose are prone to aggregation within the polymer composite, so it is quite difficult to disperse them at the nanoscale, which limits the ability to obtain sufficient reinforcing effects. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention provides a polymer composite containing cellulose fibers as a reinforcing material, which is environmentally friendly and exhibits excellent mechanical properties and high brightness.

[0007] The present invention also provides a molded article comprising the polymer composite. [Means for solving the problem]

[0008] A polymer composite and a molded article including the same according to an embodiment of the present invention will be described below.

[0009] Unless otherwise expressly stated herein, the terminology used is for the purpose of referring to particular embodiments only and is not intended to be limiting of the invention.

[0010] As used herein, the singular forms "a," "an," and "the" include the plural forms as well, unless the context clearly indicates to the contrary.

[0011] As used herein, the meaning of "comprising" is to embody certain properties, regions, integers, steps, operations, elements, components and / or components, and does not exclude the presence or addition of other certain properties, regions, integers, steps, operations, elements, components and / or groups.

[0012] As used herein, "nanofiber" or "nanofibril" refers to a fiber having a diameter on the nanometer scale, and "microfiber" refers to a fiber having a diameter on the micrometer scale. For example, the microfiber may be composed of a bundle of the nanofibers. The "diameter" of various fibers and fibrils as used herein refers to the diameter of the longest length in their cross section.

[0013] As used herein, "pulp" refers to a lignocellulosic fibrous material obtained by chemically or mechanically separating cellulose fibers from wood, fiber crops, waste paper, rags, and the like.

[0014] As used herein, "pulp fibers," "cellulose fibers," or "microcellulose fibers" refer to microfibers made of cellulose. As used herein, "cellulose nanofibers" or "nanocellulose fibers" refer to nanofibers made of cellulose.

[0015] In this specification, "fibrillation" refers to the phenomenon in which nanofibrils forming the internal structure of microcellulose fibers are loosened and the nanofibrils become fluffy on the microcellulose fibers.

[0016] As used herein, the term "fibrillated cellulose fibers" refers to microcellulose fibers in which nanofibrils having nanometer-scale diameters are formed on the microcellulose fibers as a result of the fibrillation.

[0017] According to one embodiment of the invention, Polymer matrix, a reinforcing material comprising cellulose fibers, and comprising first inorganic particles; A polymeric composite is provided that satisfies Formula 1: [Formula 1] L*≧75.0 In the above formula 1, the L* value is the lightness in the L*a*b* (CIE LAB) color system measured on a test piece made of the polymer composite using a spectrophotometer.

[0018] As a result of extensive research, the inventors have confirmed that a polymer composite obtained by dispersing a reinforcing material containing cellulose fibers and inorganic particles, which are color-concealing materials, in a polymer matrix is ​​environmentally friendly and can exhibit excellent mechanical properties and high brightness values.

[0019] The polymer composite according to an embodiment of the invention includes a reinforcing material including the cellulose fibers dispersed within the polymer matrix and the first inorganic particles.

[0020] The polymer matrix may be a polymer resin.

[0021] As an example, the polymer matrix may include one or more polymers selected from the group consisting of polyolefins, polyamides, styrene-based polymers, and polycarbonates.

[0022] Specifically, the polymer matrix may be a polyolefin such as polyethylene, polyethylene-based copolymers, polypropylene, and polypropylene-based copolymers; an aliphatic polyamide such as nylon-6 and nylon-66; an aromatic polyamide such as aramid; a styrenic polymer such as polystyrene, acrylonitrile-butadiene-styrene copolymer, styrene-maleic anhydride copolymer, styrene-acrylonitrile copolymer, and styrene-butadiene-styrene copolymer; a polycarbonate obtained by polymerizing phosgene with a polyol including bisphenol A, polyether polyol, polyester polyol, or a mixture thereof, and the like.

[0023] Preferably, the polymer matrix may comprise one or more polymer resins selected from the group consisting of polyethylene, polyethylene-based copolymers, polypropylene, polypropylene-based copolymers, nylon-6, nylon-66, aramid, polystyrene, acrylonitrile-butadiene-styrene copolymers, styrene-maleic anhydride copolymers, styrene-acrylonitrile copolymers, and styrene-butadiene-styrene copolymers, and polycarbonates.

[0024] According to an embodiment of the invention, the polymer composite comprises the first inorganic particles dispersed on the polymer matrix.

[0025] The first inorganic particles may be added as a color concealing material to improve the color of the polymer composite without deteriorating the mechanical properties of the polymer composite. For example, a polymer composite containing cellulose fiber generally has a light or deep yellow color, but the whiteness of the polymer composite can be improved by adding the first inorganic particles.

[0026] The first inorganic particles may be inorganic particles having a high refractive index. Preferably, the first inorganic particles may include one or more inorganic particles selected from the group consisting of titanium oxide, zinc oxide, boron nitride, and barium sulfate.

[0027] The first inorganic particles may be inorganic particles having an average particle size of 50 nm to 1000 nm, or 100 nm to 1000 nm, or 100 nm to 500 nm. In order to efficiently include the first inorganic particles in the polymer composite, the first inorganic particles preferably have an average particle size of 50 nm or more, or 100 nm or more. However, excessively large inorganic particles may act as defects in the polymer composite and deteriorate the mechanical properties. Therefore, the first inorganic particles preferably have an average particle size of 1000 nm or less, or 500 nm or less.

[0028] According to an embodiment of the invention, the polymer composite comprises the reinforcing material dispersed on the polymer matrix.

[0029] The reinforcing material includes cellulose fibers.

[0030] The cellulose fibers may be natural cellulose fibers obtained from wood such as coniferous trees, broad-leaved trees, etc. As an example, the cellulose fibers may be pulp fibers obtained by dissolving components other than cellulose from natural raw materials such as coniferous trees or broad-leaved trees using caustic soda, sodium sulfate, etc.

[0031] Preferably, the cellulose fibers may be microcellulose fibers comprising nanofibrils and second inorganic particles.

[0032] Cellulose nanofibers, a biodegradable and environmentally friendly natural polymer material, have recently been attracting attention as a reinforcing material for plastics. However, the process of nano-sizing (refining) microcellulose fibers to obtain nanofibers is complicated and costly, which increases the cost of polymer composites that contain cellulose nanofibers as a reinforcing material.

[0033] According to the present invention, when cellulose fibers are not nano-sized, but second inorganic particles are grown on microcellulose fibers to fibrillate the microcellulose fibers, and then the microcellulose fibers are composited with a polymer matrix, it is possible to exhibit excellent mechanical properties equivalent to those obtained when cellulose nanofibers are used.

[0034] The microcellulose fibers may be natural cellulose fibers obtained from wood such as coniferous trees and hardwoods.

[0035] Generally, fibrillation of microcellulose fibers refers to a phenomenon in which relatively large fibrils forming the membrane and internal structure of cellulose fibers are loosened by a process such as beating, and fine fibrils are fluffed on the surface.

[0036] In the present invention, the microcellulose fibers are cellulose fibers fibrillated by growing second inorganic particles on the cellulose fibers. That is, in the present invention, the microcellulose fibers containing the nanofibrils and second inorganic particles may be fibers in a state in which some of the fibrils forming the microcellulose fibers are loosened or defibrated by the growth of the second inorganic particles on the microcellulose fibers.

[0037] FIG. 1 is a schematic diagram showing enlarged views of (a) non-fibrillated microcellulose fibers and (b) microcellulose fibers containing nanofibrils and inorganic particles.

[0038] In Fig. 1(a), the non-fibrillated microcellulose fiber 100 is a fiber having a diameter on the micrometer scale. Referring to Fig. 1(b), when inorganic particles are grown on the cellulose fiber, some of the fibrils forming the microcellulose fiber 100' are loosened by the growth of the inorganic particles 20, and fibers in a fluffy state with nanofibrils 11 are formed on the microcellulose fiber 100'. In addition, the nanofibrils 11 may also be present inside the microcellulose fiber 100' due to fibrillation caused by the growth of the inorganic particles 20.

[0039] In one example, the microcellulose fibers include nanofibrils and second inorganic particles, where the nanofibrils may be attached to the surface of the microcellulose fibers or may be present within the microcellulose fibers, and the second inorganic particles are attached to the nanofibrils or attached to the surface or within the microcellulose fibers.

[0040] In the microcellulose fibers comprising the nanofibrils and second inorganic particles, the microcellulose fibers may have a diameter of 1 μm or more; and 30 μm or less, alternatively 25 μm or less, alternatively 20 μm or less, alternatively 15 μm or less, alternatively 10 μm or less. Specifically, the microcellulose fibers may have a diameter of 1 μm to 30 μm, alternatively 1 μm to 25 μm, alternatively 1 μm to 20 μm, alternatively 1 μm to 15 μm, alternatively 1 μm to 10 μm.

[0041] In the microcellulose fiber containing the nanofibrils and second inorganic particles, the nanofibrils may have a diameter of 10 nm or more, alternatively 20 nm or more, alternatively 30 nm or more, alternatively 40 nm or more, alternatively 50 nm or more; and 400 nm or less, alternatively 350 nm or less, alternatively 300 nm or less, alternatively 250 nm or less, alternatively 200 nm or less, alternatively 150 nm or less, alternatively 100 nm or less. Specifically, the nanofibrils may have a diameter of 10 nm to 400 nm, alternatively 10 nm to 350 nm, alternatively 10 nm to 300 nm, alternatively 20 nm to 300 nm, alternatively 20 nm to 250 nm, alternatively 30 nm to 250 nm, alternatively 30 nm to 200 nm, alternatively 40 nm to 200 nm, alternatively 40 nm to 150 nm, alternatively 50 nm to 150 nm, alternatively 50 nm to 100 nm.

[0042] The length of the second microcellulose fibers and the nanofibrils is not particularly limited.

[0043] The microcellulose fibers comprising the nanofibrils and second inorganic particles can be produced by adding a reducing agent, catalyst, ligand, or mixtures thereof to a mixture comprising the microcellulose fibers, the second inorganic particle precursor, and a solvent to grow the second inorganic particles from the second inorganic particle precursor distributed on the cellulose fibers.

[0044] In one example, the process includes providing a mixture including microcellulose fibers, a second inorganic particle precursor, and a solvent.

[0045] The solvent may be a compound capable of dissolving the second inorganic particle precursor and swelling the microcellulose fiber. For example, the solvent may be water, alcohol (e.g., lower alcohol such as methanol, ethanol, propanol, butanol), dimethyl sulfoxide, sodium hydroxide aqueous solution, ammonia aqueous solution, urea aqueous solution, or a mixture thereof.

[0046] The solvent can be used in an amount of 1,000 to 10,000 parts by weight per 100 parts by weight of the microcellulose fibers. Within the range of the solvent content, the microcellulose fibers are sufficiently swollen, the fluidity of the second inorganic particle precursor is ensured, and the second inorganic particle precursor can be uniformly dispersed on the microcellulose fibers.

[0047] Depending on the type of second inorganic particles grown on the microcellulose fibers, a polymer composite having various physical properties can be provided. That is, the second inorganic particle precursor can be appropriately selected according to the physical properties to be imparted to the polymer composite. As a non-limiting example, a second inorganic particle precursor capable of growing zinc oxide can be selected for the purpose of imparting antibacterial properties and heat resistance to the polymer composite.

[0048] As an example, the second inorganic particles may contain one or more elements selected from the group consisting of copper, zinc, calcium, aluminum, iron, platinum, palladium, ruthenium, iridium, rhodium, osmium, chromium, cobalt, nickel, manganese, vanadium, molybdenum, and gallium. The components of the inorganic particles may be one or more. For example, the second inorganic particles may be the above-mentioned metal particles, or oxides, nitrides, or sulfides thereof.

[0049] The second inorganic particle precursor may be a salt of one or more elements selected from the group consisting of copper, zinc, calcium, aluminum, iron, platinum, palladium, ruthenium, iridium, rhodium, osmium, chromium, cobalt, nickel, manganese, vanadium, molybdenum, and gallium. The salt may be an acetate, a chloride, a nitrate, etc. Also, the second inorganic particle precursor may be a silicon oxide precursor such as tetraethyl orthosilicate (TEOS).

[0050] The content of the second inorganic particles may be 10 to 40 parts by weight relative to 100 parts by weight of the microcellulose fibers. Specifically, the content of the second inorganic particles may be 10 parts by weight or more, or 15 parts by weight or more; and 40 parts by weight or less, or 35 parts by weight or less, or 30 parts by weight or less relative to 100 parts by weight of the microcellulose fibers. Preferably, the content of the second inorganic particles may be 10 to 40 parts by weight, or 10 to 35 parts by weight, or 15 to 35 parts by weight, or 15 to 30 parts by weight relative to 100 parts by weight of the microcellulose fibers. Therefore, the content of the second inorganic particle precursor contained in the mixture can be controlled so that the content of the second inorganic particles finally generated on the microcellulose fibers satisfies the above range. Within such a content range, the second inorganic particle precursor is uniformly distributed in the microcellulose fibers, sufficient fibrillation can be induced, and improved mechanical properties can be expressed.

[0051] The mixture is prepared by dissolving the second inorganic particle precursor in the solvent and then adding microcellulose fibers. The mixture is stirred to swell the microcellulose fibers and simultaneously distribute the second inorganic particle precursor uniformly on the swollen microcellulose fibers. The second inorganic particle precursor is attached to the microcellulose fibers by hydrogen bonds or ionic bonds.

[0052] The types and contents of the reducing agent, catalyst, and ligand added to the mixture can be appropriately selected according to the types and contents of the added second inorganic particle precursor and the second inorganic particles to be grown. As an example, the reducing agent can be sodium hydroxide (NaOH), a metal hydride-based, borohydride-based, borane-based, silane-based, hydrazine, or hydrazide-based reducing agent. The catalyst can be ammonia or urea. The ligand can be benzene-1,3,5-tricarboxylate.

[0053] 2 and 3 are scanning electron microscope (SEM) images of microcellulose fibers fibrillated by the growth of the second inorganic particles according to one manufacturing example of the present invention.

[0054] Referring to the image (a) of Figure 2, it can be seen that the second inorganic particles have grown on the microcellulose fibers and fibrillation has occurred. The image (b) of Figure 2 is a further enlarged view of a portion of the image (a).

[0055] Referring to FIG. 3, it can be seen that (a) the metal element (zinc) and (b) oxygen are uniformly distributed on the microcellulose fibers due to the growth of the second inorganic particles.

[0056] The process results in microcellulose fibers comprising the nanofibrils and second inorganic particles.

[0057] According to an embodiment of the invention, the second inorganic particles contained in the microcellulose fibers may have a diameter of 0.01 μm or more, alternatively 0.03 μm or more, alternatively 0.05 μm or more; and 10 μm or less, alternatively 7 μm or less, alternatively 5 μm or less. Preferably, the second inorganic particles may have a diameter of 0.01 μm to 10 μm, alternatively 0.03 μm to 7 μm, alternatively 0.05 μm to 5 μm.

[0058] If the particle size of the second inorganic particles contained on the microcellulose fibers is too large, the second inorganic particles may act as defects and the mechanical properties of the polymer composite may be reduced. Therefore, the particle size of the second inorganic particles is preferably 10 μm or less, 7 μm or less, or 5 μm or less.

[0059] In order to ensure sufficient fibrillation of the microcellulose fibers due to the growth of the second inorganic particles, it is preferable that the particle size of the second inorganic particles is 0.01 μm or more, or 0.03 μm or more, or 0.05 μm or more.

[0060] The second inorganic particles may be spherical particles having a diameter of 0.01 μm to 10 μm. The second inorganic particles may be columnar particles having a uniaxial diameter of 0.01 μm to 10 μm and another uniaxial diameter of 0.02 μm to 30 μm. The diameter of the second inorganic particles may be measured using a scanning electron microscope. As a non-limiting example, the diameter, minor axis diameter, or major axis diameter of 20 second inorganic particles may be measured using a scanning electron microscope, and then an average value may be calculated by excluding the maximum and minimum values.

[0061] According to an embodiment of the invention, the second inorganic particles may be included in an amount of 10 parts by weight or more, alternatively 15 parts by weight or more, and 40 parts by weight or less, alternatively 35 parts by weight or less, alternatively 30 parts by weight or less, based on 100 parts by weight of the microcellulose fibers. Preferably, the second inorganic particles may be included in an amount of 10 to 40 parts by weight, alternatively 10 to 35 parts by weight, alternatively 15 to 35 parts by weight, alternatively 15 to 30 parts by weight, based on 100 parts by weight of the microcellulose fibers.

[0062] In order to fully express the fibrillation effect and mechanical properties of the microcellulose fiber due to the growth of the second inorganic particles, it is preferable that the second inorganic particles are contained in an amount of 10 parts by weight or more, or 15 parts by weight or more, per 100 parts by weight of the microcellulose fiber.

[0063] However, if the second inorganic particles are contained in the microcellulose fibers in an excessive amount, the compatibility with the polymer matrix may decrease, which may deteriorate the mechanical properties of the polymer composite. Therefore, the second inorganic particles are preferably contained in an amount of 40 parts by weight or less, 35 parts by weight or less, or 30 parts by weight or less, per 100 parts by weight of the microcellulose fibers.

[0064] In order to ensure excellent mechanical properties, the total amount of the first inorganic particles and the second inorganic particles is preferably 1 part by weight or more per 100 parts by weight of the polymer composite. However, an excessive amount of inorganic particles may inhibit compatibility with the polymer matrix, thereby deteriorating the mechanical properties of the polymer composite. Therefore, the total amount of the first inorganic particles and the second inorganic particles is preferably 30 parts by weight or less per 100 parts by weight of the polymer composite.

[0065] For example, the total amount of the first inorganic particles and the second inorganic particles is preferably 1 part by weight or more, 2.5 parts by weight or more, or 5 parts by weight or more, and 30 parts by weight or less, or 25 parts by weight or less, or 20 parts by weight or less, or 15 parts by weight or less, relative to 100 parts by weight of the polymer composite. Specifically, the total amount of the first inorganic particles and the second inorganic particles may be 1 to 30 parts by weight, or 2.5 to 30 parts by weight, or 2.5 to 25 parts by weight, or 5 to 25 parts by weight, or 5 to 20 parts by weight, or 5 to 15 parts by weight, relative to 100 parts by weight of the polymer composite.

[0066] According to an embodiment of the invention, the cellulose fibers may be a mixture of first microcellulose fibers; and second microcellulose fibers comprising nanofibrils and second inorganic particles.

[0067] The first microcellulose fiber may be a natural cellulose fiber obtained from wood such as coniferous trees, broad-leaved trees, etc. For example, the first microcellulose fiber may be obtained by dissolving components other than cellulose from natural raw materials such as coniferous trees or broad-leaved trees using caustic soda, sodium sulfate, etc.

[0068] The first microcellulose fibers refer to microcellulose fibers that are not fibrillated compared to the microcellulose fibers containing the nanofibrils and second inorganic particles described above (i.e., fibrillated cellulose fibers).

[0069] The first microcellulose fibers may have a diameter of 10 μm to 40 μm and a length of 0.1 mm to 3 mm. Specifically, the first microcellulose fibers may have a diameter of 10 μm to 40 μm, alternatively 15 μm to 40 μm, alternatively 15 μm to 35 μm, alternatively 15 μm to 30 μm; and a length of 0.1 mm to 3 mm, alternatively 0.1 mm to 2.5 mm, alternatively 0.2 mm to 2.5 mm, alternatively 0.2 mm to 2 mm.

[0070] The first microcellulose fiber can be obtained by a wet method or a dry method. As a non-limiting example, the cellulose raw material is put into distilled water, and then ground in a mixer several times in a wet state, and then filtered under reduced pressure to obtain the first microcellulose fiber.

[0071] The second microcellulose fiber containing the nanofibrils and the second inorganic particles may be a fiber in a state in which some of the fibrils forming the second microcellulose fiber are loosened or defibrated by the growth of the second inorganic particles on the microcellulose fiber. The nanofibrils, the second inorganic particles, and the microcellulose fiber containing them are substituted for the contents described above.

[0072] According to an embodiment of the invention, the first microcellulose fibers and the second microcellulose fibers containing the nanofibrils and second inorganic particles may be contained in the polymer composite in a weight ratio of 1:0.1 to 1:3.

[0073] In other words, in order to reduce the manufacturing cost of the polymer composite and improve the mechanical properties, it is preferable that the second microcellulose fibers are contained in the polymer composite at a weight ratio of 0.1 times or more, or 0.2 times or more, based on the first microcellulose fibers.

[0074] However, if the content of the second microcellulose fibers is excessively high compared to the first microcellulose fibers, the total amount of inorganic particles contained in the polymer composite increases relatively, which may result in a decrease in the mechanical properties of the polymer composite. Therefore, it is preferable that the second microcellulose fibers are contained in the polymer composite in a weight ratio of 3 times or less, 2.5 times or less, 2 times or less, 1.5 times or less, 1.2 times or less, or 1 times or less based on the first microcellulose fibers.

[0075] Preferably, the first microcellulose fibers and the second microcellulose fibers are contained in the polymer composite in a weight ratio of 1:0.1 to 1:3, alternatively 1:0.1 to 1:2.5, alternatively 1:0.1 to 1:2, alternatively 1:0.1 to 1:1.5, alternatively 1:0.2 to 1:1.5, alternatively 1:0.2 to 1:1.2, alternatively 1:0.2 to 1:1.

[0076] According to one embodiment of the invention, the polymer composite comprises: 30 to 90% by weight of said polymer matrix; 5 to 60% by weight of the reinforcing material containing the cellulose fibers; and The first inorganic particles may be contained in an amount of 0.1 to 15% by weight.

[0077] According to another embodiment of the invention, the polymer composite comprises: 35 to 85% by weight of said polymer matrix; 10 to 55% by weight of the reinforcing material containing the cellulose fibers; and The first inorganic particles may comprise 1 to 15% by weight.

[0078] According to another embodiment of the present invention, the polymer composite comprises: 35 to 80% by weight of said polymer matrix; 10 to 50% by weight of the reinforcing material containing the cellulose fibers; and The first inorganic particles may be contained in an amount of 2.5 to 10% by weight.

[0079] In order to provide a polymer composite containing an appropriate amount of matrix, the polymer matrix is ​​preferably contained in the polymer composite at 30 wt% or more, or 35 wt% or more. And, in order to realize the improved mechanical properties according to the present invention, the polymer matrix is ​​preferably contained in the polymer composite at 90 wt% or less, or 85 wt% or less, or 80 wt% or less. Specifically, the polymer matrix may be contained in the polymer composite at 30-90 wt%, or 30-85 wt%, or 35-85 wt%, or 35-80 wt%.

[0080] In order to achieve improved mechanical properties according to the present invention, the reinforcing material containing cellulose fiber is preferably contained in the polymer composite at 5 wt% or more, or 10 wt%. However, an excessive amount of the reinforcing material may hinder compatibility with the polymer matrix, which may result in a decrease in the mechanical properties of the polymer composite. Therefore, the reinforcing material containing cellulose fiber is preferably contained in the polymer composite at 60 wt% or less, or 55 wt% or less, or 50 wt% or less. Specifically, the reinforcing material may be contained in an amount of 5 to 60 wt%, or 5 to 55 wt%, or 10 to 55 wt%, or 10 to 50 wt%.

[0081] In order to achieve improved mechanical properties and improved color according to the present invention, the first inorganic particles are preferably included in the polymer composite at 0.1 wt % or more, or 1 wt % or more, or 2.5 wt % or more. However, an excessive amount of inorganic particles may hinder compatibility with the polymer matrix, thereby reducing the mechanical properties of the polymer composite. Therefore, the first inorganic particles are preferably included in the polymer composite at 15 wt % or less, or 12.5 wt % or less, or 10 wt % or less. Specifically, the first inorganic particles may be included in the polymer composite at 0.1 to 15 wt %, or 1 to 15 wt %, or 1 to 12.5 wt %, or 2.5 to 12.5 wt %, or 2.5 to 10 wt %.

[0082] Meanwhile, the polymer composite may further include a compatibilizer dispersed on the polymer matrix, which is a component that helps the polymer matrix, the reinforcing material, and the color concealing material to blend well with each other.

[0083] The compatibilizer may be any of those known in the art, taking into consideration the specific type of the polymer matrix.

[0084] Preferably, the compatibilizer may be a modified polyolefin, which refers to a resin obtained by modifying a polyolefin with an unsaturated carboxylic acid or a derivative thereof.

[0085] The polyolefins forming the modified polyolefins can be linear olefins such as ethylene, propylene, butene, pentene, hexene, and heptene; cyclic olefins such as cyclopentene, cyclohexene, and 1,3-cyclopentadiene; and aromatic ring-substituted olefins such as styrene.

[0086] The unsaturated carboxylic acids forming the modified polyolefins can be fumaric acid, maleic acid, itaconic acid, citraconic acid, aconitic acid, and their anhydrides.

[0087] As a non-limiting example, the modified polyolefin may be polypropylene or polyethylene grafted with 0.1-10 wt % maleic anhydride.

[0088] Such modified polyolefins can further improve the compatibility of cellulose fibers with the polymer matrix, thereby improving the mechanical properties of the polymer composite.

[0089] In order to achieve appropriate compatibility, the compatibilizer may be included in the polymer composite at 0.1 wt % or more, or 1 wt % or more, or 5 wt % or more. However, an excessive amount of the compatibilizer may deteriorate the mechanical properties of the polymer composite. Therefore, the compatibilizer is preferably included in the polymer composite at 15 wt % or less, or 10 wt % or less. Specifically, the compatibilizer may be included in the polymer composite at 0.1 to 15 wt %, or 1 to 15 wt %, or 1 to 10 wt %, or 5 to 10 wt %.

[0090] According to an embodiment of the invention, the polymer composite is obtained by mixing the above-mentioned components in a mixer and then curing the mixture. The polymer composite is also prepared by preparing a composition in which the reinforcing material containing cellulose fiber and the first inorganic particles are mixed, and mixing the composition with the polymer matrix. As a non-limiting example, the above-mentioned components are mixed in a batch mixer at 100 to 180°C, and then a master batch in the form of pellets is prepared, and the master batch is fed into an extruder for extrusion and injection to obtain the polymer composite.

[0091] According to an embodiment of the invention, the polymer composite contains the above-mentioned components, and thus is environmentally friendly and exhibits improved mechanical properties and high brightness values.

[0092] In one example, the polymer complex satisfies the following formula 1: [Formula 1] L*≧75.0 In the above formula 1, the L* value is the lightness in the L*a*b* (CIE LAB) color system measured on a test piece made of the polymer composite using a spectrophotometer.

[0093] The L*a*b* (CIE LAB) color system is one of the methods of expressing color tones for evaluating hues, and is a color space that represents colors seen by the eye, as formulated by the International Commission on Illumination (CIE). This lightness (L* value) is an index that indicates the tendency of brightness, and ranges from 0 to 100.

[0094] Preferably, the polymer composite may have a high L* value of 75.0 or more, alternatively 80.0 or more, alternatively 85.0 or more, alternatively 90.0 or more. Specifically, the polymer composite may have an L* value of 75.0 to 99.5, alternatively 75.0 to 99.0, alternatively 80.0 to 98.5, alternatively 80.0 to 98.0, alternatively 85.0 to 98.0, alternatively 90.0 to 98.0, alternatively 90.0 to 97.5, alternatively 90.1 to 97.5, alternatively 90.1 to 97.0. The L* value may be a value measured in reflection mode on a test piece of an appropriate size using a spectrophotometer.

[0095] As another example, the polymer composite may have an Izod impact strength of 15 J / m or more, measured according to the standard test method of ASTM D256 (23° C., hammer head 3.00 J) on a 63.5 mm×12.7 mm×3.2 mm test piece having an ASTM D256 notch made of the polymer composite. Specifically, the polymer composite may have an Izod impact strength of 15 J / m or more, alternatively 17 J / m or more, alternatively 19 J / m or more; and 70 J / m or less, alternatively 65 J / m or less, alternatively 60 J / m or less, alternatively 55 J / m or less. Preferably, the polymer composite exhibits an Izod impact strength of 15 J / m to 70 J / m, alternatively 15 J / m to 65 J / m, alternatively 17 J / m to 65 J / m, alternatively 19 J / m to 65 J / m, alternatively 19 J / m to 60 J / m, alternatively 19 J / m to 55 J / m.

[0096] As another example, the polymer composite may have a tensile strength of 25 MPa or more, measured according to the standard test method of ASTM D638-5 on a dog-bone shaped test piece (or a dumbbell shaped test piece) made of the polymer composite. Preferably, the polymer composite may exhibit a tensile strength of 25 MPa to 70 MPa, or 25 MPa to 65 MPa, or 28 MPa to 63 MPa, or 30 MPa to 63 MPa.

[0097] ASTM D638 provides a standard test method for determining the tensile properties of plastics. The tensile properties of the polymer composites are determined using ASTM D638 specimen type 5. ASTM D638 is performed by applying a tensile force to the specimen and measuring the tensile properties of the specimen under stress. This is done on a conventional tensile testing machine at a constant pulling rate ranging from 1 to 500 mm / min until the specimen fails (yields or breaks). The tensile strength is the amount of force that can be applied until the specimen yields or breaks.

[0098] As another example, the polymer composite may have a flexural strength of 50 MPa or more, measured on a test piece of the polymer composite having dimensions of 80 mm x 10 mm x 4 mm, according to the standard test method of ISO 178. Preferably, the polymer composite may exhibit a flexural strength of 50 MPa to 95 MPa, alternatively 50 MPa to 90 MPa, alternatively 52 MPa to 90 MPa, alternatively 52 MPa to 88 MPa.

[0099] The polymer composite may have a flexural modulus of 1.5 GPa or more, measured on a test piece of the polymer composite having dimensions of 80 mm x 10 mm x 4 mm, in accordance with the standard test method of ISO 178. Preferably, the polymer composite may exhibit a flexural modulus of 1.5 GPa to 4.0 GPa, or 1.6 GPa to 4.0 GPa, or 1.6 GPa to 3.8 GPa, or 1.7 GPa to 3.8 GPa, or 1.7 GPa to 3.6 GPa.

[0100] ISO 178 provides a standard test method for determining flexural properties for plastics by performing a three-point bend test. In a three-point bend test, a force is applied to the midpoint of a rectangular specimen that is supported freely at both ends. The applied force is measured by a load cell, and the resulting deflection is measured by crosshead displacement or a direct strain measurement device. This is performed in a conventional flexural tester, applying a force to the specimen at a constant rate in the range of 1-500 mm / min. The flexural strength is the maximum flexural stress achieved during the bend test. The flexural stress is measured by the flexural tester as a function of the applied load, span, specimen width, and specimen thickness.

[0101] As another example, the polymer composite may have the Izod impact strength of 15 J / m to 70 J / m, the tensile strength of 25 MPa to 70 MPa, and the flexural strength of 50 MPa to 95 MPa.

[0102] As another example, the polymer composite may have the Izod impact strength of 17 J / m to 65 J / m, the tensile strength of 28 MPa to 63 MPa, and the flexural strength of 52 MPa to 90 MPa.

[0103] As another example, the polymer composite may have the Izod impact strength of 19 J / m to 55 J / m, the tensile strength of 30 MPa to 63 MPa, and the flexural strength of 52 MPa to 88 MPa.

[0104] As another example, the polymer composite may have the Izod impact strength of 27 J / m to 55 J / m, the tensile strength of 50 MPa to 63 MPa, and the flexural strength of 65 MPa to 88 MPa.

[0105] Meanwhile, according to another embodiment of the invention, a molded article including a polymer composite is provided.

[0106] The molded article containing the polymer composite is environmentally friendly and exhibits excellent mechanical properties.

[0107] The molded article may be manufactured by a conventional processing method using the polymer composite as a raw material, for example, by injection molding, extrusion molding, calendar molding, etc. using a raw material composition including the polymer composite.

[0108] As an example, a molded article including the polymer composite can be manufactured by injection molding. The polymer composite, which has been molten through the plasticization and flow steps, is filled into a mold cavity by a plunger, and then undergoes a cooling step to solidify it. The mold is equipped with a pressure sensor, a temperature sensor, a hot runner system, etc. A separate cooling line may be present to solidify the molten material. The plunger is retracted, and the solidified molded article may be separated from the mold using an ejector pin.

[0109] Preferably, the molded article may be a lightweight material for automobiles, such as an interior material for automobiles or an exterior material for automobiles. For example, the molded article may be one or more interior and exterior materials for automobiles selected from the group consisting of a dashboard, a door trim, a battery tray, a bumper, a luggage trim, a door opening trim, a headliner, a rear shelf, a tonneau cover, a sun visor, an assist grip, a console box, a fender panel, an oil pan, a wheel house, a side skirt, a garnish, an electric part, an engine cover, a seat belt cover, a switch button, and a center facia.

[0110] In addition, the molded product can be used in various fields such as interior and exterior materials and packaging materials for home appliances. Effect of the Invention

[0111] The polymer composite according to the present invention contains cellulose fiber as a reinforcing material and is environmentally friendly, and exhibits excellent mechanical properties and high brightness. [Brief description of the drawings]

[0112] [Figure 1] FIG. 2 is a schematic diagram showing enlarged views of (a) non-fibrillated microcellulose fibers and (b) microcellulose fibers containing nanofibrils and second inorganic particles. [Diagram 2]1 is a scanning electron microscope (SEM) image of cellulose fibers fibrillated by the growth of second inorganic particles according to Preparation Example 2. [Diagram 3] 1 is a scanning electron microscope (SEM) image of cellulose fibers fibrillated by the growth of second inorganic particles according to Preparation Example 2. [Figure 4] FIG. 1 is a comparative SEM image of (a) fibrillated microcellulose fibers according to Production Example 3 and (b) fine cellulose fibers composited with particles according to Production Example 4. [Diagram 5] This is an SEM image of (a) and (b) in FIG. 4 taken at a higher magnification. [Figure 6] FIG. 1 is a diagram showing the standard for a dog-bone shaped test piece (or a dumbbell shaped test piece) for measuring tensile strength according to ASTM D638 Type V (unit: mm). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0113] The functions and effects of the present invention will be described in more detail below with reference to specific examples of the present invention. However, these are presented as examples to aid in understanding the invention, and do not limit the scope of the invention in any way. EXAMPLES

[0114] Manufacturing Example 1 (First preparation of microcellulose fibers) Hardwood kraft pulp (cellulose fiber) was prepared as a cellulose raw material. 20 g of the pulp was added to 1000 g of distilled water, and the mixture was crushed three times in a mixer in a wet state, and then filtered under reduced pressure to prepare a first microcellulose fiber (diameter of 15 μm to 30 μm and length of 0.2 mm to 2 mm).

[0115] Manufacturing Example 2 (Production of second microcellulose fibers containing nanofibrils and second inorganic particles) As a cellulose raw material, hardwood kraft pulp (cellulose fiber) was prepared. An aqueous solution was prepared by dissolving 20 g of zinc acetate in 1000 g of distilled water. 20 g of the pulp was added to the aqueous solution and stirred at 500 rpm for 2 hours to obtain a mixture.

[0116] The mixture was added with 7.2 g of sodium hydroxide (NaOH) as a reducing agent at room temperature and stirred at 500 rpm for 2 hours to grow second inorganic particles (ZnO) on the pulp. The content of the second inorganic particles was confirmed to be 27 parts by weight per 100 parts by weight of the pulp.

[0117] Scanning electron microscope (SEM) observation confirmed that fibrillation had occurred in the pulp area where the second inorganic particles (ZnO) had grown, as shown in Figure 2(a). Analysis of the SEM image confirmed that the second inorganic particles had a particle size of approximately 0.1μm to 1μm.

[0118] The above method yielded microcellulose fibers containing nanofibrils and second inorganic particles.

[0119] Production Example 3 (Production of second microcellulose fibers containing nanofibrils and second inorganic particles) Softwood kraft pulp fiber (cellulose fiber) was prepared as a cellulose raw material. 20 g of the pulp fiber was added to an aqueous solution of 20 g of zinc acetate dissolved in 1000 g of distilled water, and the mixture was stirred at 500 rpm for 2 hours to prepare a mixture. Zinc acetate was attached to the swollen pulp fiber by hydrogen bonds and ionic bonds in the mixture.

[0120] 3.6 g of sodium hydroxide (NaOH) was added to the mixture at room temperature and stirred at 500 rpm for 2 hours to grow second inorganic particles (ZnO) on the pulp fibers. The content of the second inorganic particles was confirmed to be 15 parts by weight per 100 parts by weight of the pulp.

[0121] When examined using a scanning electron microscope, it was confirmed that fibrillation had occurred in the areas of the pulp fibers where particles (ZnO) had grown, as shown in Figures 4(a) and 5(a).

[0122] The above method yielded microcellulose fibers containing nanofibrils and second inorganic particles.

[0123] Production Example 4 (Production of fine cellulose fibers) As a cellulose raw material, the same softwood kraft pulp fiber as in Example 1 was prepared. The surface of the pulp fiber was oxidized using 2,2,6,6-tetramethylpiperidinyl-1-oxy radical (TEMPO) as a catalyst to obtain oxidized pulp.

[0124] 1 g of the oxidized pulp was dispersed in 99 g of distilled water and subjected to a pulverization (fibrillation) treatment in a mixer for 30 minutes to obtain an aqueous dispersion of pulverized cellulose with a concentration of 1%.

[0125] A zinc acetate solution was prepared by dissolving 20 g of zinc acetate in 1000 g of distilled water. A sodium hydroxide solution was prepared by dissolving 3.6 g of sodium hydroxide (NaOH) in 10 ml of distilled water.

[0126] 100 g of the fine cellulose aqueous dispersion was stirred at 15° C. while 50 ml of the zinc acetate aqueous solution and 10 ml of the sodium hydroxide aqueous solution were added, and the mixture was stirred at 500 rpm for 2 hours to prepare a composite of zinc oxide (ZnO) particles and fine cellulose.

[0127] As a result of observing using a scanning electron microscope, as shown in FIG. 4-(b) and FIG. 5-(b), it was confirmed that the composite of zinc oxide particles and fine cellulose of Preparation Example 4 had poor particle dispersion because the nanofibers were clumped together due to the strong binding force and aggregation between the fine cellulose.

[0128] Example 1 20 wt% of the first microcellulose fiber according to Preparation Example 1, 10 wt% of the second microcellulose fiber including nanofibrils and second inorganic particles according to Preparation Example 2, 55 wt% of polypropylene, 5 wt% of the first inorganic particles (titanium oxide, average particle size 350 nm), and 10 wt% of a compatibilizer were added to a batch mixer and mixed at 180° C. for 20 minutes to prepare a master batch in the form of pellets. Maleic anhydride-grafted polypropylene was used as the compatibilizer.

[0129] The master batch was fed into a twin screw extruder and extruded through a compounding process. The mixture obtained by the extrusion was fed into an injector again and extruded to obtain polymer composite test pieces and molded products (luggage trim for automobiles).

[0130] Example 2 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that 15 wt% of the first microcellulose fiber according to Preparation Example 1, 15 wt% of the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 2, 55 wt% of polypropylene, 5 wt% of the first inorganic particles (titanium oxide, average particle size 350 nm), and 10 wt% of a compatibilizer were added to a batch mixer.

[0131] Example 3 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 3 was used instead of the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 2.

[0132] Example 4 25 wt% of the first microcellulose fiber according to Preparation Example 1, 5 wt% of the second microcellulose fiber including nanofibrils and second inorganic particles according to Preparation Example 2, 55 wt% of polypropylene, 5 wt% of the first inorganic particles (titanium oxide, average particle size 350 nm), and 10 wt% of a compatibilizer were added to a batch mixer and mixed at 180° C. for 20 minutes to prepare a master batch in the form of pellets. Maleic anhydride-grafted polypropylene was used as the compatibilizer.

[0133] The master batch was fed into a twin screw extruder and extruded through a compounding process. The mixture obtained by the extrusion was fed into an injector again and extruded to obtain polymer composite test pieces and molded products (luggage trim for automobiles).

[0134] Example 5 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that 20 wt% of the first microcellulose fiber according to Preparation Example 1, 10 wt% of the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 2, 57.5 wt% of polypropylene, 2.5 wt% of the first inorganic particles (titanium oxide, average particle size 350 nm), and 10 wt% of a compatibilizer were added to a batch mixer.

[0135] Example 6 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that 20 wt% of the first microcellulose fiber according to Preparation Example 1, 10 wt% of the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 2, 52.5 wt% of polypropylene, 7.5 wt% of the first inorganic particles (titanium oxide, average particle size 350 nm), and 10 wt% of a compatibilizer were added to a batch mixer.

[0136] Example 7 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that 20 wt% of the first microcellulose fiber according to Preparation Example 1, 10 wt% of the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 2, 50 wt% of polypropylene, 10 wt% of the first inorganic particles (titanium oxide, average particle size 350 nm), and 10 wt% of a compatibilizer were added to a batch mixer.

[0137] Example 8 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that 30 wt% of the first microcellulose fiber according to Preparation Example 1, 15 wt% of the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 2, 40 wt% of polypropylene, 5 wt% of the first inorganic particles (titanium oxide, average particle size 350 nm), and 10 wt% of a compatibilizer were added to a batch mixer.

[0138] Example 9 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that 15 wt% of the first microcellulose fiber according to Preparation Example 1, 10 wt% of the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 2, 60 wt% of polypropylene, 5 wt% of the first inorganic particles (titanium oxide, average particle size 350 nm), and 10 wt% of a compatibilizer were added to a batch mixer.

[0139] Example 10 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that 10 wt% of the first microcellulose fiber according to Preparation Example 1, 5 wt% of the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 2, 70 wt% of polypropylene, 5 wt% of the first inorganic particles (titanium oxide, average particle size 350 nm), and 10 wt% of a compatibilizer were added to a batch mixer.

[0140] Example 11 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that 10 wt% of the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 2, 80 wt% of polypropylene, 5 wt% of the first inorganic particles (titanium oxide, average particle size 350 nm), and 5 wt% of a compatibilizer were added to a batch mixer.

[0141] Example 12 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that 30 wt% of the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 2, 55 wt% of polypropylene, 5 wt% of the first inorganic particles (titanium oxide, average particle size 350 nm), and 10 wt% of a compatibilizer were added to a batch mixer.

[0142] Comparative Example 1 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that 20 wt% of the first microcellulose fiber according to Preparation Example 1, 10 wt% of the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 2, 60 wt% of polypropylene, and 10 wt% of a compatibilizer were added to a batch mixer.

[0143] Comparative Example 2 Polymer composite test pieces and molded articles were obtained in the same manner as in Example 1, except that 30 wt % of the hardwood kraft pulp (cellulose fiber) used in Preparation Example 1 that was swollen in water, 60 wt % of polypropylene, and 10 wt % of a compatibilizer were added to a batch mixer.

[0144] Comparative Example 3 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that 15 wt% of the first microcellulose fiber according to Preparation Example 1, 15 wt% of the second microcellulose fiber containing nanofibrils and second inorganic particles according to Preparation Example 2, 60 wt% of polypropylene, and 10 wt% of a compatibilizer were added to a batch mixer.

[0145] Comparative Example 4 Polymer composite test pieces and molded products were obtained in the same manner as in Example 1, except that 30 wt % of the fine cellulose fiber of Preparation Example 4, 60 wt % of polypropylene, and 10 wt % of the compatibilizer were added to a batch mixer.

[0146] Test Example (1) Fiber diameter The diameter of the cellulose fibers from the preparation examples was measured using a scanning electron microscope. Specifically, for microcellulose fibers, the diameters of 10 microfibers per sample were measured and expressed as a range excluding the maximum and minimum values; for nanofibrils, the diameters of 20 nanofibrils per sample were measured and expressed as a range excluding the maximum and minimum values.

[0147] Furthermore, unlike the examples, in Production Example 4, the pulp fibers were finely pulped (defibrated) and then composited with particles, and the diameter of the nanofibrils in Production Example 4 in Table 1 below means the diameter of the finely pulped cellulose after it has been composited with particles.

[0148] (2) Tensile test The following test specimen (FIG. 6) was prepared according to the standard of ASTM D638 Type V. The test specimen was left in a constant temperature and humidity room controlled at a temperature of 23° C. and a relative humidity of 50% for 24 hours and then used for the tensile test.

[0149] The tensile strength (MPa), tensile modulus (GPa) and elongation at break (%) of the test specimens were measured using an Instron Universal Testing Machine (UTM) in accordance with the standard test method of ASTM D638. Based on the standard test method of ASTM D638, the grip spacing for holding the test specimens at both ends was set to 25.4 mm, and the test was performed at a constant tensile speed of 5 mm / min at a crosshead speed.

[0150] (3) Bending test A test piece with a size of 80 mm x 10 mm x 4 mm was prepared according to the standard test method of ISO 178. The test piece was left in a constant temperature and humidity room controlled at a temperature of 23°C and a relative humidity of 50% for 24 hours and then used for a bending test.

[0151] The test specimens were measured for flexural strength (MPa), flexural modulus (GPa), and flexural deformation at break (%) using an Instron Universal Testing Machine (UTM) in accordance with the standard test method of ISO 178. Based on ISO 178, a three-point bending test fixture was used to perform the bending test under the test conditions of a supports span of 46 mm and a crosshead speed of 5 mm / min.

[0152] (4) Impact strength A test piece having a size of 63.5 mm x 12.7 mm x 3.2 mm and having a notch according to the ASTM D256 standard was prepared. The Izod impact strength of the test piece was measured by the standard test method of ASTM D256 (23°C, hammer head 3.00 J) using a digital impact tester (QM (700A), manufactured by QMESYS).

[0153] (5) Hue measurement The test pieces were measured for hue according to the L*a*b* (CIE LAB) color system using a spectrophotometer (model name: Ci7860, manufacturer: X-rite). Test pieces measuring 63.5mm x 12.7mm x 3.2mm according to ASTM D256 were prepared, and measurements were taken three times in reflection mode, after which the average value was recorded.

[0154] [Table 1]

[0155] [Table 2]

[0156] [Table 3]

[0157] [Table 4]

[0158] Referring to Tables 2 to 4, it was confirmed that the polymer composites according to the examples exhibited equivalent or improved mechanical properties and high brightness values ​​compared to the polymer composites according to the comparative examples.

[0159] Although the cellulose fibers produced in Preparation Example 4 had particles grown on the fine cellulose, when they were composited with a polymer matrix in Comparative Example 4, excessive re-agglomeration of the fine cellulose and particles occurred. The test pieces in Comparative Example 4, which showed poor dispersibility due to re-agglomeration, generally showed poor physical properties. [Explanation of symbols]

[0160] 100,100' microcellulose fiber 11 Nanofibrils 20 Second inorganic particle

Claims

1. 30-90% by weight of polymer matrix, 5-60% by weight of a reinforcing material comprising cellulose fibers, and Contains 0.1 to 15 wt % of first inorganic particles; Satisfying the following formula 1, The cellulose fibers are microcellulose fibers comprising nanofibrils and second inorganic particles; The microcellulose fibers are fibrillated by growing second inorganic particles on the cellulose fibers, the nanofibrils being bonded to the surface of the microcellulose fibers; the second inorganic particles being bonded to the nanofibrils or to the surface or interior of the microcellulose fibers; the first inorganic particles include one or more inorganic particles selected from the group consisting of titanium oxide, zinc oxide, boron nitride, and barium sulfate; The second inorganic particles include one or more metal particles selected from the group consisting of copper, zinc, calcium, aluminum, iron, silver, platinum, palladium, ruthenium, iridium, rhodium, osmium, chromium, cobalt, nickel, manganese, vanadium, molybdenum, magnesium, strontium, titanium, zirconium, hafnium, and gallium, or silicon oxide particles. Polymer complex: [Formula 1] L*≧75.0 In the above formula 1, the L* value is the lightness in the L*a*b* (CIE LAB) color system measured on a test piece made of the polymer composite using a spectrophotometer.

2. The polymer composite according to claim 1 , wherein the second inorganic particles are contained in an amount of 10 to 40 parts by weight based on 100 parts by weight of the microcellulose fibers.

3. 2. The polymer composite of claim 1, wherein the second inorganic particles include spherical particles having a diameter of 0.01 μm to 10 μm; columnar particles having one axis diameter of 0.01 μm to 10 μm and another axis diameter of 0.02 μm to 30 μm; or a mixture thereof.

4. 2. The polymer composite of claim 1, wherein the microcellulose fibers have a diameter between 1 μm and 30 μm; and the nanofibrils have a diameter between 10 nm and 400 nm.

5. 2. The polymer composite of claim 1, wherein the cellulose fibers are a mixture of first microcellulose fibers; and second microcellulose fibers comprising nanofibrils and second inorganic particles.

6. The polymer composite of claim 5, wherein the first microcellulose fibers have a diameter of 10 μm to 40 μm and a length of 0.1 mm to 3 mm.

7. The polymer composite of claim 5, wherein the cellulose fibers comprise the first microcellulose fibers and the second microcellulose fibers comprising the nanofibrils and second inorganic particles in a weight ratio of 1:0.1 to 1:

3.

8. The polymer composite according to claim 5, wherein the total amount of the first inorganic particles and the second inorganic particles is 1 to 30 parts by weight based on 100 parts by weight of the polymer composite.

9. The polymer composite according to claim 1 , wherein the first inorganic particles have an average particle size of 50 nm to 1000 nm.

10. 2. The polymer composite of claim 1, wherein the polymer composite has an L* value of 90.0 to 98.

0.

11. 2. The polymer composite of claim 1, wherein the polymer matrix comprises one or more polymer resins selected from the group consisting of polyethylene, polyethylene-based copolymers, polypropylene, polypropylene-based copolymers, nylon-6, nylon-66, aramid, polystyrene, acrylonitrile-butadiene-styrene copolymers, styrene-maleic anhydride copolymers, styrene-acrylonitrile copolymers, and styrene-butadiene-styrene copolymers, and polycarbonates.

12. An Izod impact strength of 15 J / m or more, measured in accordance with the standard test method of ASTM D256 on a test piece having a size of 63.5 mm x 12.7 mm x 3.2 mm and having an ASTM D256 notch made of the polymer composite; A tensile strength of 25 MPa or more measured according to the standard test method of ASTM D638-5 on a test piece made of the polymer composite according to ASTM D638-5; and A flexural strength of 50 MPa or more measured according to the standard test method of ISO 178 on a test piece having dimensions of 80 mm x 10 mm x 4 mm made of the polymer composite. The polymer composite of claim 1 ,

13. the L* value being from 90.0 to 98.0; An Izod impact strength of 19 J / m to 55 J / m, measured according to the standard test method of ASTM D256 (23° C., hammer head 3.00 J) on a test piece having a size of 63.5 mm×12.7 mm×3.2 mm and having an ASTM D256 notch made of the polymer composite; A tensile strength of 30 MPa to 63 MPa measured according to the standard test method of ASTM D638-5 on a test piece made of the polymer composite according to ASTM D638-5; and A bending strength of 52 MPa to 88 MPa measured according to the standard test method of ISO 178 on a test piece of 80 mm x 10 mm x 4 mm made of the polymer composite. The polymer composite of claim 1 ,

14. A molded article comprising the polymer composite of claim 1.

15. The molded article according to claim 14, which is an interior or exterior material for an automobile.

16. The molded products include dashboards, door trims, battery trays, bumpers, luggage trims, door opening trims, headliners, rear shelves, tonneau covers, sun visors, assist grips, console boxes, fender panels, oil pans, wheel houses, side skirts, garnishes, and electric parts.

16. The molded article according to claim 15, which is one or more automotive interior and exterior materials selected from the group consisting of seat covers, engine covers, seat belt covers, switch buttons, and center fascias.

Citation Information

Patent Citations

  • Resin composition

    JP2012201767A

  • Product including composition of calcium carbonate fine particle and fiber

    JP2015199658A

  • Variable displacement pump

    JP2017053273A